Knowledge and practice on fluoride utilization and tea drinking habits of three regions in the Philippines - Parajas, I.L (The Journal of the Philippine Dental Association)
This is a study to determine the knowledge and practice on fluoride utilization and tea drinking habits of three regions. A total of 2,648 respondents ages 12, 30-39 and 40 years above were interviewed by trained aides and Public Health Dentists supervised by the Regional Dental Supervisors using a structured questionnaire. Results showed that about half of the respondents were aware of fluoride, and that it prevents tooth decay and make the tooth stronger. Toothpaste was cited as the most common source of fluoride. Only one fourth of respondents drink tea and they do it for stomach ache and diarrhea. Still others take it for slimming and as a coffee substitute. Wild tea or Tsaang Gubat is known only by one fifth of respondents and a very low percent are aware of its dental benefits. Half of the respondents later at the end of the interview stated that they will drink tea and recommend it for their family, relatives and friends. In general, the younger age group knew more about fluoride, its source and benefits. More of the older age groups drank tea compared to the young. A well planned and intensive information campaign integrated into the preventive oral health program is needed to promote the use of fluorides and tea.